Evaluation of Glutathione S-Transferase Activity in Venous and Finger-Prick Blood in Healthy Smoking and Non-Smoking Men in Kuwait - Almutairi, Abeer; Akkam, Yazan; Alajmi, Mohammad (Jordan Journal of Pharmaceutical Sciences, 2019)
BACKGROUND: Smoking has long been hypothesized to be an inducer of oxidative stress; hence antioxidant enzymes such as glutathione S-transferases (GSTs) are an important defense line against prospective oxidative cell damage. OBJECTIVES: This work investigated whole blood GST activity with respect to tobacco smoking. Also, it evaluated the possibility of using capillary blood (finger-prick) as a route of sampling for GST activity in comparison to the conventional venous blood sampling. METHODS: Whole blood GST activities were measured from healthy volunteers, as well as from distinct categories of smokers classified according to type of tobacco and number of cigarettes. RESULTS: No statistically significant difference was detected in the GST level finger-prick vs. venous blood. The GST activity was 5.249 ± 0.2 U/g/Hb for control group, 9.6 ± 1.71 U/g/Hb for one pack smokers, 7.2 ± 1.6 U/g/Hb for more than one pack smokers, and 3.7 ± 0.24 U/g/Hb for Hookah smokers. CONCLUSIONS: This study provides evidence that finger brick sampling can replace venous blood for measuring GST activity. Also proofs that tobacco smoking (especially Hookah) has an extreme influence on GST activity, which may lead to neutralizing the GST mechanism, and subsequently rendering an insufficient self-defense against oxidative stress.